Novel Oral Anticoagulant versus Warfarin in Cancer Patients with Atrial Fibrillation: An 8-Year Population-Based Cohort Study - Wu, Victor Chien-Chia (J Cancer, 2020)
Background: Cancer patients with atrial fibrillation (AF) were excluded in the major clinical trials. We therefore investigated the efficacy and safety of novel oral anticoagulant (NOAC) versus warfarin in these patients. Methods: Data were retrieved from Taiwan National Health Insurance Research Database during 2010-2017 for patients with AF, excluding those without cancer or >1 cancer, not using anticoagulant, switching of agents, patients age <18, and cancer and AF diagnosed >1 month apart. Primary outcomes are ischemic stroke (IS)/systemic embolism (SE), GI bleeding, major bleeding, intracranial hemorrhage (ICH), acute myocardial infarction (AMI), and death from any cause at 6 months and 1 year. Results: After exclusion criteria and propensity score matching, there were 336 patients in each group. Patients on NOAC had significantly reduced IS/SE (HR=0.45, 95% CI=0.25-0.82), major bleeding (HR=0.21, 95% CI=0.05-0.96), and no ICH at 6 months. In addition, IS/SE (HR=0.42, 95% CI=0.24-0.74), major bleeding (HR=0.26, 95% CI=0.09-0.76), and no ICH at 1 year compared to patients on warfarin. There was no difference on GI bleeding, AMI, and death from any cause at 6 months and at 1 year. Conclusion: In cancer patients with AF, NOAC were associated with significant reduced IS/SE, major bleeding, and ICH compared to warfarin.